Metabolomic markers predictive of hepatic adaptation to therapeutic dosing of acetaminophen - Sonn, Brandon J.; Heard, Kennon J.; Heard, Susan M.; D'Alessandro, Angelo; Reynolds, Kate M.; Dart, Richard C.; Rumack, Barry H.; Monte, Andrew A. (Clinical toxicology (Philadelphia, Pa.), 2022)
Drug induced liver injury (DILI) remains a prominent global issue and acetaminophen (APAP) overdose represents a common cause of hepatic injury and DILI. Transient alanine aminotransferase (ALT) elevations have been documented while adhering to recommended daily dosing. However, no metabolites have been identified in pre-treatment samples predicting which patients will develop these transient increases. This was a secondary analysis of samples collected from a parent study describing the course of ALT levels in subjects receiving therapeutic APAP dosing. Two hundred and four subjects recruited from Denver, Colorado received 4 g APAP/daily for at least 16 days. Subjects were grouped by ALT at any monitored time point above 60 units/L (n = 25) vs. no increase (n = 179). Serum samples from days 0, 7, 16, and 31 were run on ultra-high performance liquid chromatography mass spectrometry. We report the metabolomic results of samples analyzed prior to APAP administration and over time. Significant changes in metabolite and demographic variable expressions were explored using t-tests with false discovery rate correction, chi square, and partial least squares discriminant analyses. Within pre-treatment day 0 samples, allantoate and ornithine were significantly elevated in subjects of the ALT elevation group (p = .032). Baseline ALT (p = .011) and alkaline phosphatase (p = .006) were also significant. These metabolites were significant independent of race, ethnicity, gender, or BMI. Allantoate and ornithine are directly involved in pathways related to nitrogen release and urea production. Further investigation into alterations in the glutathione metabolism and urea cycle pathways may lead to a greater understanding of the mechanisms associated with hepatic adaptation for a variety of pharmaceuticals.